Respon pertumbuhan dan produksi rumput Brachiaria decumbens terhadap pemberian kompos Trichoderma sp - Maria Erviana Kusuma; - Kastalani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
This study aims to determine the growth and production response of Brachiaria decumbens on application of Trichoderma sp. compost and to know the dosage of Trichoderma sp. compost which gives the best results on growth and production of Brachiaria decumbens. This research was conducted in the field research of Animal Husbandry Faculty, Christian University Palangka Raya using Completely Randomized Design with single factor experiment that was the dosage of Trichoderma sp. compost that is 0 ton ha-1, 10 ton ha-1, 20 ton ha-1, 30 ton ha-1 and 40 ton ha-1. The result of this research is the giving of Trichoderma sp. compost does not give effect to the number of chicks Brachiaria decumbens but it has significant effect on the high of crop on 6 and 8 week after planting and production of Brachiaria decumbens. Trichoderma sp. compost 10 ton ha-1, 20 ton ha-1, 30 ton ha-1 and 40 ton ha-1 gave the same effect on the production of the Brachiaria decumbens.